Enhancing displacement ventilation performance: Proposal of a new portable air purifying displacement ventilation unit - Essa Aya; Yamanaka Toshio; Choi Narae; Kobayashi Tomohiro; Kobayashi Noriaki; Komori Miharu; Matsui Nobuki; Okamoto Tetsuya; Arakawa Takeshi; Yamoto Yuki; Otaka Shougo (E3S Web of Conferences, 2023)
Displacement Ventilation (DV) has been known as an energy saving system as it relies on buoyancy force to draw hot air upwards to be displaced by cool air. The main strength of DV that recommends it nowadays is that a well-designed DV system prevents mixing of contaminants as they are dragged along the hot air upward flow leaving the occupied zone, breathing zone in particular, clean. However, the system’s effectiveness is lowered in large rooms due to design problem such as difficult balance between sufficient supply flow volume and low inlet velocity, furniture arrangement acting as obstacles, or room geometry. Hence, DV feasibility is limited to small and mid-size rooms. In order to expand the DV potential and applicability to all space types and sizes, this study proposes a portable DV air purifying unit. The unit is designed to be mobile consisting of air recycling unit with no duct connections which widens the range of use to cover a variety of indoor spaces as well as small to medium sized room. The unit has two main functions, one is reinforcing the temperature gradient as stratification crucial for DV, and the second is purifying recycled air. To investigate the effectiveness and feasibility of the proposed DV unit, block model calculations and CFD analysis were conducted. In a basic office room, multiple cases were calculated and assessed in terms of temperature distribution and stratification height. In addition, exhaled contaminants were simulated and the contaminant concentration was used as an indicator for the air quality. Observations on the proposed unit’s performance and design aspects were highlighted.